Biphasic short time heat degradation of the blue microalgae protein phycocyanin from Arthrospira platensis. (March 2019) - Böcker, L.; Ortmann, S.; Surber, J.; Leeb, E.; Reineke, K.; Mathys, A.
Abstract: Stability of colorants is concerning for food coloring matrices, particularly for the only natural blue food coloring, phycocyanin. The Spirulina -based microalgal extract is mainly comprised of heat sensitive protein-chromophore complexes, C-phycocyanin and allophycocyanin. Although frequently encountered in food processing, the impact of short time heat treatments has not been studied systematically. Here, phosphate buffered phycocyanin solution was heated in batch and emerging continuous processing systems, both characterized with high surface-to-volume ratios allowing isothermal conditions with residence times down to 5 s. Absorption scans revealed biphasic degradation of phycocyanin color activity to about 30% within 30 s at T ≥ 70 °C. Kinetic modelling of the color decay via an nth order approach contradicts previously assumed linear first order kinetics with a best fitting empirical reaction order of n = 6. It shows that decay in phycocyanin color activity is not a single process but encompasses C-phycocyanin and allophycocyanin aggregate disintegration and denaturation. Industrial relevance: Central to this study is the color stability of phycocyanin, which is a high value component, derived from the emerging food source microalgae. It is also the only naturally obtained blue food coloring available to the food industry. Insights could be gained on the color degradation kinetics by treating an industry relevant formulation in batch and emerging scalable continuous systems via micro process engineering. This data will directly support food research and development activities to optimize and minimize blue color losses within multiple product categories. Highlights: Relevant short time heating of high value phycocyanin formulation Color activity of phycocyanin degrades in 30 s at T ≥ 70 °C to 30% initial intensity. Denaturation of phycocyanin does not follow log10 linear degradation kinetics. Degradation kinetics best described with empirical reaction order of n = 6